Effects of omega 3 on doxorubicin-induced cardiotoxicity in an experimental rabbit model (Research, Society and Development, 2021)
To evaluate the effects of the use of omega 3 at different doses, following the response through stereological and morphometric evaluations in doxorubicin-induced acute cardiotoxicity in an experimental rabbit model. Thirty healthy adult New Zealand rabbits were divided into six groups with different doses of omega 3 treatment, GT125, GT500 and GT 2000, receiving doses of 125mg / kg, 500mg / kg and 2000mg / kg, respectively. The induction of acute cardiotoxicity with doxorubicin was treated for six days prior to intravenous administration of 10mg / kg single dose. Then, the animals were euthanized and myocardial samples were collected for stereological and morphometric evaluations. The stereological evaluation showed an increase in the transverse area of ​​cardiomocytes between the SHAM and GT2000 groups and an increase in the interstitial collagen volume density between the SHAM and GT500 and SHAM and GT2000 groups. The omega 3 500mg/kg dose has the potential to attenuate the fibrotic effects of doxorubicin use and the use of a single dose of 10mg/kg doxorubicin can be used as an acute dilated cardiomyopathy induction protocol in an experimental model using rabbits.